Pelaksanaan Pengangkatan dan Pemindahan Pejabat Administrator Oleh Pejabat Pembina Kepegawaian di Lingkungan Pemerintah Daerah - Nur Ghufran Azoumy; Dodi Haryono; Separen Separen (Pattimura Legal Journal)
Introduction: Administrator Officials are appointed and determined by the Staff Supervisory Officer. The implementation of the appointment and transfer of administrator officials within the Karimun Regency Government is considered not running optimally. There are administrator officials who sit in office but not in accordance with the requirements specified in PP No.11 of 2017 concerning Civil Servant Management.